PERANAN GOOD CORPORATE GOVERNANCE DALAM PENCEGAHAN FRAUD DI RUMAH SAKIT UMUM DAERAH KOTA MAKASSAR TAHUN 2022 - Indah Zulkartini.P; Dian Ekawaty; Mangindara Mangindara; Nurmulia Wunaini Ngkolu (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
The study investigates about the role of the good corporate governance in the prevention at the RSUD Makassar that city, at RSUD city makassar is something normal happened yet the hospital immediately repair it if there are data eror. The purpose of this study to see how the role of good corporate governance in terms of watch Transparency ( oppennes ), Accountabillity (of the function clarity), Responsibillity (compliance ). Researchused in this research was qualitative research was conducted with the approach descriptive which is in the form of words written or spoken, to the total number of informants in this research as many as 8 people with the data this research obtained through observation in-depth interviews that direct observation was in direct and the study documentation during the survey in progress. The research result show that the city of makassar at the hospital have to apply the principle of good corporate governance in terms of the delivery of information in watchdog Transparency , clarity function in Accountabillity, structure compliance legislationin Responsibillity, independence in Indepedency , and in Fariness kesetaraan .